Analisis Pesan Dakwah Motion Graphic pada Akun Instagram @Muhammadnuzuldzikri - Annisa Fatihatul Ikhsan; Aida Ramadhani; Muhammad Haikal Fikri; Rendi Rendi (Pusat Riset dan Inovasi Nasional, 2024)
In this modern era, preaching is not only done on the pulpit, but also through print and electronic media, especially social media such as Instagram. Many people are involved in spreading the preaching through these platforms. One form of interesting preaching content is motion graphic video, a combination of 2D animation representing moving infographics. Motion graphics combine elements of illustration, typography, photography, and videography with animation to strengthen the delivery of the message. This study aims to determine the preaching messages in the motion graphic videos uploaded by Ustadz Muhammad Nuzul Dzikri through the Instagram account @muhammadnuzuldzikri, which include the themes of faith, morals, and Islamic law. The method used is descriptive qualitative with content analysis techniques and observation of 9 motion graphic videos uploaded from December 2024 to January 2025.